Successive relaying for large MIMO amplify‐and‐forward relay networks. (7th March 2018) - Peng, Hong; Su, Changran; Zhang, Yu
Summary: In this paper, we consider a large relay network with one source, K relays and M users, where the source and relays are equipped with W and N antennas, respectively. We propose an amplify‐and‐forward successive relaying protocol in which the relays are divided into 2 groups to successively help transmission to M users. Achievable sum rate of the proposed protocol is derived and found to scale as M l o g ( K ) + O ( 1 ) when N and M are fixed and K → ∞ . On the other hand, when M and K are fixed and N → ∞, the achievable sum rate scales as M l o g ( N ) + O ( 1 ) . Therefore, the scaling law of the achievable sum rate coincides with the capacity scaling law of the considered network. Then, both precoding at the source and grouping of the relay nodes are jointly optimized to further improve the proposed protocol. Numerical results show that the proposed successive relaying protocol can outperform the conventional 2‐slot relaying protocol and the proposed joint optimization scheme for source precoding and relay grouping bring considerable rate gain. Abstract : We propose an amplify‐and forward successive relaying protocol in which the relays are divided into 2 groups to successively help transmission to multiple users. The protocol achieves the network capacity scaling law, which only requires statistic CSI at source and user terminals and local CSI at each relay. Moreover, the source precoder and relay grouping are jointly optimized to further improve its performance.